Pengelolaan Sampah dan Limbah B3 dalam Perspektif Hukum Lingkungan: Disharmonisasi Regulasi dan Tantangan Prinsip Kehati-hatian - Syifa Sofia Agustin; Andini Nurul S; Garri Selastiani (Journal of Legal, Political, and Humanistic Inquiry, 2025)
Environmental degradation resulting from the management of domestic waste and Hazardous and Toxic Waste (B3) has become an existential challenge for Indonesia in achieving its sustainable development goals. This article aims to conduct a critical review of the regulatory framework for waste and B3 management in Indonesia, particularly following the enactment of Law Number 11 of 2020 on Job Creation (now established under Law No. 6 of 2023) and its correlation with Law Number 32 of 2009 on Environmental Protection and Management (UU PPLH). The research method employed is normative legal research utilizing both a statute approach and a conceptual approach. The results of the study indicate that although Indonesia possesses a comprehensive set of legal instruments ranging from Government Regulation (PP) No. 22 of 2021 to specific regulations concerning medical and electronic waste there remains a disharmony between central and regional policies in field implementation. The primary critique in this article is directed at the paradigm shift from a stringent licensing system to a risk-based approach. The author argues that the relaxation of oversight in B3 waste disposal procedures has the potential to undermine the precautionary principle, which serves as a pillar of international environmental law.